Tinjauan Implementasi Pembangunan Berkelanjutan: Pengelolaan Sampah Kota Kendari - Faturachman Alputra Sudirman; Phradiansah Phradiansah (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2019)
Waste management issues is the primary concern of the Kendari City Government, considering to become a liveable city namely the sustainable development of Kendari City. This study discusses the challenges of implementing a waste management policy based sustainable development in Kendari City. One of the goals of sustainable development on the 2030 agenda is to reduce the impact of the urban environment with the percentage of municipal reliable waste handling indicators. The purpose of this study is to determine the implementation of waste management policies using the concept of policy implementation by Edwards III and to link it to the concept of sustainable development and the 2030 agenda of Sustainable Development Goals (SDGs). This study used a qualitative method, in which data was collected through interviews and documentation, the findings in this study that the implementation of waste management policies in Kendari City was quite excellent in the aspects of communication, resources, disposition, and bureaucratic structure. However, various challenges were also present in every aspect of policy implementation. Overall, the implementation of waste management policies also takes into account sustainable development in economic, social and environmental aspects and was by efforts to achieve SDGs Goal 11, where 73.30 per cent of urban waste has been handled.